Adherence to the cMIND and AIDD diets and their associations with anxiety in older adults in China - Qi, Yana; Xue, Xinyu; Chen, Ningsu; Gong, Jie; Mu, Dongyu; Zhao, Kai; Zhao, Mengnan; Li, Youping; Shi, Lei; Yu, Jiajie (Frontiers in Nutrition, 2025)
IntroductionAnxiety is highly prevalent among older adults, and dietary interventions targeting nutrition may offer effective, practical strategies for preventing mental disorders. This study aimed to explore the association between the cMIND diet, anti-inflammatory dietary diversity (AIDD), and the risk of anxiety in older adults.MethodsA cross-sectional analysis was conducted using data from the 2018 Chinese Longitudinal Healthy Longevity Survey (CLHLS). Anxiety symptoms were assessed using the Generalized Anxiety Disorder (GAD-7) scale, while adherence to the cMIND diet and AIDD was evaluated through a food frequency questionnaire. Univariable and multivariable logistic regression analyses were performed to examine associations between dietary patterns and anxiety risk, with odds ratios (ORs) and 95% confidence intervals (CIs) reported. Random forest analysis was used to identify key factors influencing anxiety, and sensitivity analyses were conducted to test the robustness of the results.ResultsA total of 13,815 participants aged 65 and older were included, with 1,550 (11.2%) identified with anxiety. Multivariable logistic models indicated that adherence to the cMIND diet or higher AIDD was associated with a 16–26% reduced risk of anxiety, with the adjusted ORs (95% CIs) for the cMIND diet ranging from 0.75 (0.64–0.87) to 0.75 (0.61–0.91), and for AIDD from 0.74 (0.62–0.88) to 0.84 (0.73–0.96). Sensitivity analyses confirmed the stability of these findings. Depression and sleep quality were identified as the most important factors contributing to anxiety, while diet was one of the few modifiable factors.ConclusionThis study provides evidence supporting the association between diet and anxiety in older adults, highlighting the potential of promoting healthy dietary patterns and targeted nutritional interventions as effective strategies for improving mental health in the aging population.